Assessment of digital enhancement filters in the radiographic determination of alveolar bone level - Matheus Lima Oliveira; Luciana Moraes; Jonathan Nicholas Santos Pereira; Guilherme Monteiro Tosoni (Wolters Kluwer Medknow Publications, 2015)
Context: Recent studies have emphasized the advantages of digital radiographic imaging systems for periodontal evaluation. Because digital enhancement filters are designed to improve image quality, the real impact of such improvement on diagnostic accuracy needs to be evaluated for different clinical tasks. Aims: To assess the efficacy of digital enhancement filters in the radiographic determination of the alveolar bone level. Materials and Methods: Twenty-four digital periapical radiographs were obtained from mandibular sites with alveolar bone loss. Two enhancement filters-perio and invert-were applied separately and jointly on all radiographic images. The alveolar bone level was measured by consensus agreement of two examiners in 55 sites on the standard and enhanced radiographic images. A single examiner obtained the actual measurements on the dry mandible by using a periodontal probe and a digital caliper. For each assessment site, three measurements were obtained and averaged. One-way analysis of variance for differences between the actual measurements and radiographic image groups was performed (α = 0.05). Results: The digital radiographic measurements overestimated the actual by approximately 0.2 mm. There was no statistically significant difference between radiographic image groups. Furthermore, none of them differed from the actual measurements. Conclusion: Under the tested conditions, the perio and invert enhancement filters did not interfere with the efficacy of the radiographic images, which were accurate in determining the alveolar bone level.